The phenomenon of Islamic nasyid groups in Malaysia: establishment, impacts & challenges: Rabbani, Raihan and Hijjaz as a case study - Zaroum, AbdulHamid Mohamed Ali (s.n, 2015)
This paper attempts to shed some light on Islamic Nasyid groups in Malaysia, in particular RABBANI, RAIHAN AND HIJJAZ. With the emergence of globalization and its entertainment aspect, and due to the huge influence of modernization on the society especially among the youth, there was, indeed, a need for an alternative entertainment. And, as far as Muslims are concerned, the most effective way in this regard was, to a great extent, Islamic Nasyid. Entertainment itself has been an area of great discussion and dispute among Muslim scholars throughout the ages all over the world. In Malaysia, the issue of allowing or disallowing entertainment specifically songs and music is no longer a big issue. As a matter of fact, entertainment is part of the traditions and culture of the Muslims in this part of the world. Nevertheless, the major concern here is that what kind of songs and music do Nasyid groups present? Could Islamic Nasyid be an alternative to the conventional or non-Islamic songs? Is it possible for Nasyid performance to be viewed as an act of worship? To what extent Nasyid groups are contributing in the Islamization of entertainment and enhancement of Islamic awareness in Malaysian society?? The focus of this research will be on: (1) The historical background of RABBANI, RAIHAN AND HIJJAZ Nasyid groups (2) The role these groups have been playing in creating Islamic awareness; (3) The Islamization of songs and music as promoted by these three groups; (4) The challenges these Nasyid groups are facing in terms of publication and audience attendance etc.; and (5) The future of Islamic Nasyid in Malaysia. This research is expected to provide important findings that will enhance Islamic awareness among the society members. Besides, it is hoped that this research will highlight the effectiveness of Islamic Nashyd in Malaysia specially in this border less globalized village .